Optimalisasi Produksi melalui Peramalan dan Perencanaan Agregat (Studi Kasus pada CV AKJ) - Shafa, Lizha Nur; Miharja, Rediawan (Jurnal Salingka Nagari, 2025)
This study aims to address the issue of unmet production targets by implementing optimization through forecasting and aggregate planning. The research method used in this study is the mix method research method. Data collection techniques include interviews, observations, documentation, and literature review. The results indicate that the moving average forecasting method is the most appropriate, based on error measurement using the Mean Absolute Percentage Error (MAPE). Furthermore, aggregate planning using the chase strategy yields the lowest total production cost, amounting to Rp 595,406,796, with an average monthly cost of Rp 49,617,233—representing a saving of Rp 3,459,226 compared to the previous strategy.